How are companies attracting and adapting to gen Z, while retaining millennials?: consulting proposal about the optimization of the global talent offering framework at Zurich insurance - Freitas, Mariana Besteiro Oliveira de (2022)
This paper analyses how companies are nowadays adapting to the new generation so called Gen Z and, complementary, how they are retaining Millennials. To understand this, two surveys were sent out. On the main one, nine workers from different companies provided information on their organization has been adapting to Gen Z. On the second one, seventy-four respondents provided feedback and stated their preferences related to the workplace. Results show that companies have been struggling with change, adaptation, and retention rates.